Sheep Are Susceptible to the Bovine Adapted Transmissible Mink Encephalopathy Agent by Intracranial Inoculation and Have Evidence of Infectivity in Lymphoid Tissues - Cassmann, Eric D.; Moore, S. Jo; Smith, Jodi D.; Greenlee, Justin J. (Frontiers in Veterinary Science, 2019)
Transmissible mink encephalopathy (TME) is a food borne prion disease. Epidemiological and experimental evidence suggests similarities between the agents of TME and L-BSE. This experiment demonstrates the susceptibility of four different genotypes of sheep to the bovine adapted TME agent by intracranial inoculation. The four genotypes of sheep used in this experiment had polymorphisms corresponding to codons 136, 154, and 171 of the prion gene: V136R154Q171/VRQ, VRQ/ARQ, ARQ/ARQ, and ARQ/ARR. All intracranially inoculated sheep without comorbidities (15/15) developed clinical signs and had detectable PrPSc by immunohistochemistry, western blot, and enzyme immunoassay (EIA). The mean incubation periods in sheep with bovine adapted TME correlated with their relative genotypic susceptibility. There was peripheral distribution of PrPSc in the trigeminal ganglion and neuromuscular spindles; however, unlike classical scrapie and C-BSE in sheep, sheep inoculated with the bovine TME agent did not have immunohistochemically detectable PrPSc in the lymphoid tissue. To rule out the presence of infectivity, the lymph nodes of two sheep genotypes, VRQ/VRQ and ARQ/ARQ, were bioassayed in transgenic mice expressing ovine prion protein. Mice intracranially inoculated with retropharyngeal lymph node from a VRQ/VRQ sheep were EIA positive (3/17) indicating that sheep inoculated with the bovine TME agent harbor infectivity in their lymph nodes despite a lack of detection with conventional immunoassays. Western blot analysis demonstrated similarities in the migration patterns between bovine TME in sheep, the bovine adapted TME inoculum, and L-BSE. Overall, these results demonstrate that sheep are susceptible to the bovine adapted TME agent, and the tissue distribution of PrPSc in sheep with bovine TME is distinct from classical scrapie.